1998
DOI: 10.1073/pnas.95.7.3786
|View full text |Cite
|
Sign up to set email alerts
|

A third distinct tumor necrosis factor receptor of orthopoxviruses

Abstract: Cowpox virus Brighton red strain (CPV) contains a gene, crmD, which encodes a 320-aa tumor necrosis factor receptor (TNFR) of 44% and 22% identity, respectively, to the CPV TNFR-like proteins, cytokine response modifiers (crm) CrmB and CrmC. The crmD gene was interrupted in three other cowpox strains examined and absent in various other orthopoxviruses; however, four strains of ectromelia virus (ECT) examined contained an intact crmD (97% identity to CPV crmD) and lacked cognates of crmB and crmC. The protein,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
93
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(94 citation statements)
references
References 36 publications
0
93
0
1
Order By: Relevance
“…and others 1998). On the other hand, CPV GRI-90 has four different TNFR-like genes (Shchelkunov et al, 1998), three of which express a vTNFR (Hu et al, 1994 ;Smith et al, 1996 ;Loparev et al, 1998). A soluble vTNFR has been predicted from sequence similarity in lymphocystis disease virus (Tidona & Darai, 1997), a large DNA iridovirus that infects fish, consistent with the conservation of TNF throughout evolution (Beck & Habicht, 1991).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…and others 1998). On the other hand, CPV GRI-90 has four different TNFR-like genes (Shchelkunov et al, 1998), three of which express a vTNFR (Hu et al, 1994 ;Smith et al, 1996 ;Loparev et al, 1998). A soluble vTNFR has been predicted from sequence similarity in lymphocystis disease virus (Tidona & Darai, 1997), a large DNA iridovirus that infects fish, consistent with the conservation of TNF throughout evolution (Beck & Habicht, 1991).…”
Section: Discussionmentioning
confidence: 96%
“…CrmC is a 25 kDa protein that is expressed late during infection and binds TNF but not LTα (Smith et al, 1996). CrmD was identified recently in CPV and ectromelia virus and is a late, 46 kDa protein that is secreted as disulphide-linked complexes and binds TNF and LTα (Loparev et al, 1998). vTNFRs from myxoma virus (M-T2) and CPV (CrmC) bind TNF with high affinity and block TNF-mediated cytolysis in vitro (Schreiber et al, 1996 ;Smith et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…1), was previously expressed from a bacterial vector and was shown to bind TNF (17). We expressed EV CrmD from VV Western Reserve, a strain that does not encode vTNFRs (20), and found that recombinant CrmD was secreted into the medium, bound human 125 I-TNF, and inhibited human TNF biological activity (Fig.…”
mentioning
confidence: 96%
“…4 and 5; www.poxvirus.org). Cowpox virus (CPV), a rodent virus that infects other species sporadically, encodes all four vTNFRs (15)(16)(17)(18). Ectromelia virus (EV) is a highly virulent mouse pathogen that causes mousepox, a disease similar to smallpox, and encodes CrmD only (19).…”
mentioning
confidence: 99%
“…Published by New Century Science Press [20] 。另外,这个蛋白可以发挥 IκB 样区"替代品"的作用,以干扰 NF-κB 移位到细胞核 [21] 。牛痘病毒(CPXV)蛋白 CrmB、-C 和-D 能够作为可溶性的 TNF-α受体阻断配体和 受体的相互作用 [22][23][24][25] 。痘苗病毒 N1、A52R 和 B14 蛋白都有一个共同的类似 Bcl-2 的折叠结构,该结构可 抑制 IKK 复合物的活化 [26][27][28][29] ,而 M2L 蛋白可抑制 ERK2 和 K1L 阻止 IκBα的降解 [20] 。传染性软疣病毒所…”
Section: 逃逸宿主抗感染免疫的机制未见报道。unclassified